سیرت نبویؐ اور غیر مسلموں سے تعلقات: نئے مباحث - ڈاکٹر غطریف شہباز نقوی (FIKR-O NAZAR فکر ونظر, 2012)
The paper explores new approaches in modern Sirah studies regarding the relations of Holy Prophet ﷺ with non Muslims. The classical Sirah literature mostly presented this aspect in a way, that is difficult to appreciate for modern audience concerned with inter-faith harmony. According to classical approach, the Holy Prophet ﷺ disassociated himself from the rest of society comprising of pagans of Mecca and other non-Muslim Arab tribes, including Jews and Christians. Muslim jurists (most of them if not all) also ruled that the relations between Muslims and non Muslims are essentially of a permanent hostility and that reconciliation between Muslim and non Muslim governments could only be established in a contingent and pressing situation, which should be of a temporary nature. This concept is echoed in the major part of Muslim discourse throughout the Muslim history. The paper argues that prominent modern Sirah writers and scholars like Dr. Mohammad Hamidullah, Abu Zuhra, Mohammad Al-Ghazali, Hussain Haickal, Tariq Ramadan, Yasin Mazhar Siddiqi and Dr. Mahmood Ahmad Ghazi differ with the classical view. After exploring classical Sirah literature and close examination of collections of Ahadith, they conclude that relationship between the Prophet ﷺ and his peer Arab and non Arab pagans and non Muslims was based on a principled Dawah approach and not on absolute hostility and enmity.